2020
DOI: 10.3389/fvets.2020.587926
|View full text |Cite
|
Sign up to set email alerts
|

Brachyspira hyodysenteriae Infection Reduces Digestive Function but Not Intestinal Integrity in Growing Pigs While Disease Onset Can Be Mitigated by Reducing Insoluble Fiber

Abstract: Swine dysentery (SD) induced by Brachyspira hyodysenteriae manifests as mucohemorrhagic diarrhea in pigs, but little is known about the changes that occur to the gastrointestinal tract during this disease. It is thought that dietary fibers alter disease pathogenesis, although the mechanisms of action are unclear. Thus, the objectives of this study were to characterize intestinal integrity, metabolism, and function in pigs during SD and determine if replacing insoluble fiber with fermentable fibers mitigates di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 55 publications
1
16
0
Order By: Relevance
“…We have previously demonstrated that replacing corn DDGS with highly fermentable sugar beet pulp and resistant potato starch delays onset and reduces severity of B. hyodysenteriae challenge [ 16 ]. However, longitudinal growth performance during the recovery phase of disease was not evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously demonstrated that replacing corn DDGS with highly fermentable sugar beet pulp and resistant potato starch delays onset and reduces severity of B. hyodysenteriae challenge [ 16 ]. However, longitudinal growth performance during the recovery phase of disease was not evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Alterations in dietary insoluble fiber have been shown to affect the intestinal microbiome in pigs and may predispose to the development of SD in previous studies. 8,30,80 In the past few decades, commercial swine diets have increased the use of distiller’s dried grains with solubles (DDGS), which is a coproduct of biofuel production. 73 DDGS have relatively more insoluble dietary fiber than whole corn and this fiber passes through to the colon where it is fermented.…”
mentioning
confidence: 99%
“…Mitochondria were isolated from ileum and colon tissue via differential centrifugation as previously described [ 16 ]. Washed mitochondria were resuspended in 3 mL mitochondrial wash buffer, protein concentrations were determined via BCA assay (Thermofisher Scientific), and were diluted to a protein concentration of 2 mg/mL and stored at 4 ℃ until use [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Mitochondrial reactive oxygen species (ROS) production was determined in isolated mitochondria using a 2′,7′-Dichlorofluorescin diacetate (DCFH) assay described previously [ 16 18 ]. Mitochondrial hydrogen peroxide production was calculated from a hydrogen peroxide standard curve based on fluorescence values of DCFH.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation